Impulsivity and reward and punishment sensitivity among patients admitted to a specialized inpatient eating disorder treatment program - Martinelli, Mary K.; Schreyer, Colleen C.; Vanzhula, Irina A.; Guarda, Angela S. (Frontiers in Psychiatry, 2024)
Introduction Eating disorders (EDs) are conceptualized as disorders of under- and over-control, with impulsivity reflecting under-control. Extant research indicates that impulsivity and related factors such as reward sensitivity and punishment sensitivity may serve as trait-level transdiagnostic risk and/or maintenance factors in EDs. Findings on impulsivity and reward and punishment sensitivity by diagnosis are mixed and research on the relationship between these factors and ED symptoms, hospital course, and treatment outcomes is limited. Methods Participants (N = 228) were patients admitted to a specialized inpatient behavioral treatment program for EDs who agreed to participate in a longitudinal study and completed self-report measures of impulsivity, reward sensitivity, and punishment sensitivity at admission. Weight and ED symptomatology were measured at admission and discharge. Hospital course variables included length of stay and premature treatment dropout. Results Impulsivity was lower in individuals with anorexia nervosa (AN) restricting type compared to those with AN binge/purge type or bulimia nervosa; no other group differences were observed. Higher impulsivity was associated with greater bulimic symptoms on the Eating Disorder Inventory 2 (EDI-2) at admission. Impulsivity was not related to ED symptoms, weight outcomes, length of hospital stay, or treatment dropout at program discharge. Conclusion Impulsivity may help distinguish restrictive versus binge/purge EDs, but does not necessarily relate to discharge outcomes in an intensive inpatient ED program. Findings from this study provide novel contributions to the literature on personality traits in EDs and have important clinical implications. Results suggest that patients with higher levels of impulsivity or reward and punishment sensitivity can be expected to respond to inpatient treatment. Suggestions for future research are discussed.